2021
DOI: 10.1038/s41598-021-85537-3
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth dynamics of graphene grown by radio frequency plasma-enhanced chemical vapor deposition

Abstract: We investigated the nucleation and grain growth of graphene grown on Cu through radio frequency plasma-enhanced chemical vapor deposition (RF-PECVD) at different temperatures. A reasonable shielding method for the placement of copper was employed to achieve graphene by RF-PECVD. The nucleation and growth of graphene grains during PECVD were strongly temperature dependent. A high growth temperature facilitated the growth of polycrystalline graphene grains with a large size (~ 2 μm), whereas low temperature indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Translating these performance enhancements to functional substrates at the wafer scale will require directly grown graphene synthesis approaches on the substrate of interest. For example, CVD approaches using small molecules, activated precursors, or plasma-enhanced CVD processes show promise for reducing the graphene synthesis temperature and may be a route for graphene growth directly on GaAs and other technologically important compound semiconductors.…”
Section: Discussionmentioning
confidence: 99%
“…Translating these performance enhancements to functional substrates at the wafer scale will require directly grown graphene synthesis approaches on the substrate of interest. For example, CVD approaches using small molecules, activated precursors, or plasma-enhanced CVD processes show promise for reducing the graphene synthesis temperature and may be a route for graphene growth directly on GaAs and other technologically important compound semiconductors.…”
Section: Discussionmentioning
confidence: 99%
“…Translating these performance enhancements to functional substrates at wafer scale will require direct graphene synthesis approaches on the substrate of interest. For example, CVD approaches using small molecules [23], activated precursors [24], or plasmaenhanced CVD processes [25][26][27] show promise for reducing the graphene synthesis temperature, and may be a route for graphene growth directly on GaAs and other technologically important compound semiconductors.…”
Section: Discussionmentioning
confidence: 99%
“…At a deposition temperature of 400 °C and postdeposition annealing up to 800 °C under Ar flow, crystal growth and graphitization are obtained on Cu and Ni foils and interestingly on NaCl. Recently, the growth of Gr grains on Cu substrate using the radio frequency PECVD (RF-PECVD) at different temperatures has been reported [43]. ese authors demonstrated the fabrication of large polycrystalline Gr grains at high temperatures and a relatively long dwell time.…”
Section: Chemical Vapor Deposition Chemical Vapor Depositionmentioning
confidence: 99%